Conventional and Novel Technologies in the Production of Dairy Bioactive Peptides - Murtaza, Mian Anjum; Irfan, Shafeeqa; Hafiz, Iram; Ranjha, Muhammad Modassar A. N.; Rahaman, Abdul; Murtaza, Mian Shamas; Ibrahim, Salam A.; Siddiqui, Shahida Anusha (Frontiers in Nutrition, 2022)
Background In recent years, researchers have focused on functional ingredients, functional foods, and nutraceuticals due to the rapidly increasing interest in bioactive components, especially in bioactive peptides. Dairy proteins are a rich and balanced source of amino acids and their derived bioactive peptides, which possess biological and physiological properties. In the dairy industry, microbial fermentation and enzymatic hydrolysis are promising methods for producing bioactive peptides because of their rapid efficiency, and mild reaction conditions. However, these methods utilize less raw material, take long reaction time, result in low yields, and low activity products when used alone, which pose industry to seek for novel methods as pretreatments to increase the yield of bioactive peptides. Scope and Approach This review emphasizes the production of peptides from the dairy proteins and discusses the potential use of novel technologies as pretreatments to conventional methods of bioactive peptides production from dairy proteins, including the mechanisms of novel technologies along with respective examples of use, advantages, limitations, and challenges to each technology. Key Findings and Conclusion Noteworthily, hydrolysis of dairy proteins liberate wide-range of peptides that possess remarkable biological functions to maintain human health. Novel technologies in the dairy industry such as ultrasound-assisted processing (UAP), microwave-assisted processing (MAP), and high pressure processing (HPP) are innovative and environmentally friendly. Generally, novel technologies are less effectual compared to conventional methods, therefore used in combination with fermentation and enzymatic hydrolysis, and are promising pretreatments to modify peptides’ profile, improve the yields, and high liberation of bioactive peptides as compared to conventional technologies. UAP is an innovative and most efficient technology as its mechanical effects and cavitation change the protein conformation, increase the biological activities of enzymes, and enhance enzymatic hydrolysis reaction rate.